Perception of pregnant women on maternity care services at the Volta Regional Hospital, Ghana - Konlan, Kennedy Diema; Kombat, Joseph M.; Japiong, Milipaak; Konlan, Kennedy Dodam (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternity period is crucial and sensitive in the life of women due to various physiological changes that take place in the body during pregnancy and after. These changes need close monitoring to help optimize maternal and foetal health. This study explored pregnant women’s perceptions of maternity care services in the Volta Regional Hospital. Methods: Multiparous women (170) in the Ante Natal Clinic responded to a pretested questionnaire. The sample size was determined using Fischer’s formula for sample size calculation. Respondents were chosen using the convenient sampling method. The data was analysed using Statistical Package for Social Sciences version 20 in to descriptive statistics. Results: This study identified that women (42.5%) were never encouraged by health care providers to bring their partners during antenatal visits. Pregnant women (62.9%) reported that health care professionals did not allow their support persons including their husbands to be with them during labour. Women (34.1%) during labour were sometimes assaulted while 2.9% were always assaulted. Majority (74.2%) of the women received this five cardinal services that included vitamin K, eye care, cord care, bathing and immunization during the post natal period as 60.7% were introduced to family planning by midwives. Conclusions: Partner involvement in maternal health care needs to be encouraged by midwives to improve support from partners during pregnancy, labour and the post natal period. Support persons should be allowed to stay with women during labour to give the necessary support and encouragement and also take part in decision making concerning women’s care.